Reliability of hydropneumodrives for metal cutting equipment - Fatieieva, N. M.; Fatyeyev, O. M.; Poliakov, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The reliability of hydropneumodrives largely determines the safety of machine tools, metal cutting equipment, the movement of transport vehicles, and the flight of modern passenger aircraft, and their failures can in some cases lead to accidents. The design stage is crucial in ensuring reliability. The main tasks of reliability research and calculation at this stage can be divided into three groups. First, it is a justification of reliability requirements for the main elements of the hydraulic pneumatic actuator (the task of reliability norming). This task is solved at an early stage of design and involves the preliminary development of the unit structure and justification of design principles. Secondly, it is to ensure the reliability of the elements and the unit as a whole. This group of tasks includes research and quantitative assessment of the efficiency of possible ways to ensure reliability; selection of basic design characteristics, statistical reserves of durability and longevity, stability reserves and other indicators; comparative analysis of options and selection of optimal designs. Thirdly, these are control calculations of the unit's reliability according to the design documentation. Algorithms for the distribution of normalised reliability indices at the design stage for hydropneumodrives implemented by the standard positional structure method and the minimisation method are obtained. Algorithms allow already at the early stages of hydropneumodrive design to normalise reliability indices, which makes it possible to obtain optimal solutions of reliability issues at the subsequent stages of development of the drive life cycle. The methods of calculation and determination of design relations for finding quantitative characteristics of failure-free indices of designed hydropneumodrives, implemented by the method of standard positional structure and the method of minimisation, are selected, which allows designing highly reliable hydropneumodrives for new metal cutting equipment. Evaluation of reliability indicators of hydropneumodrives at the stage of preliminary design allows to make a rational choice of structural scheme and parameters, to select appropriate materials and elements of scheme realisations.

Надійність гідропневмоприводів у великій мірі визначає безпеку роботи верстатів, металорізального устаткування, руху транспортних машин, польотів сучасних пасажирських літаків і їх відмови в ряді випадків можуть привести до аварій. Етап проектування є визначальним у забезпеченні надійності. Основні завдання дослідження і розрахунку надійності на цьому етапі умовно можна розділити на три групи. По-перше, обгрунтування вимог по надійності до основних елементів гідропневмоприводу (завдання нормування надійності). Це завдання вирішується на ранній стадії проектування і передбачає попередню розробку структури агрегату і обгрунтування принципів проектування. По-друге, забезпечення надійності елементів і агрегату в цілому. Ця група завдань включає дослідження і кількісну оцінку ефективності можливих способів забезпечення надійності; вибір основних проектних характеристик, статистичних запасів міцності і довговічності, запасів стійкості та інших показників; порівняльний аналіз варіантів і вибір оптимальних конструкцій. По-третє, контрольні розрахунки надійності агрегату за проектною документацією. Отримано алгоритми для розподілу нормованих показників надійності на етапі проектування для гідропневмоприводів, реалізованих методом стандартної позиційної структури і методом мінімізації. Алгоритми дозволяють вже на ранніх стадіях проектування гідропневмоприводів нормувати показники надійності, що дає можливість отримувати оптимальні рішення питань надійності на наступних етапах розробки життєвого циклу приводу. Обрано методи розрахунку і визначення розрахункових співвідношень для знаходження кількісних характеристик показників безвідмовності проектованих гідропневмоприводів, реалізованих методом стандартної позиційної структури і методом мінімізації, що дозволяє проектувати високонадійні гідропневмоприводи нового металорізального обладнання. Оцінка показників надійності гідропневмоприводів на етапі ескізного проектування дозволяє здійснити раціональний вибір конструктивної схеми і параметрів, підібрати відповідні матеріали і елементи реалізацій схем.
Надійність гідропневмоприводів метальрізального устаткування
Keywords: reliability; hydropneumodrive; probability of failure-free operation; failure rate; method of distribution of reliability norms; vulnerability factor; надійність; гідропневмопривод; ймовірність безвідмовної роботи; інтенсивність відмов; метод розподілу норм надійності; коефіцієнт уразливості